THE EFFECT OF LIQUIDITY, LEVERAGE, AND COMPANY SIZE ON COMPANY VALUE WITH CSR AS A MEDIATING VARIABLE IN MINING AND AGRICULTURE SECTOR COMPANIES IN 2018-2024 - Nuryanti, Sarah Putri; Nengsih, Titin Agustin; Sudharyati, Neneng; Faturahman, Faturahman; Prayogo, Youdhi; Prayogo, Youdhi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study examines the influence of liquidity, leverage, and company size on company value with Corporate Social Responsibility (CSR) as a mediating variable. The focus of the research is on companies in the mining and agricultural sectors that have a high level of social and environmental exposure, so this topic has become very relevant. The problem studied is whether CSR is able to mediate the relationship between financial indicators (liquidity, leverage, and company size) and company value. The novelty of this research lies in the integration of CSR as a mediating variable in the context of two industrial sectors with a wide impact, which has not been extensively researched in depth, especially in Indonesia. The method used is quantitative with  the Structural Equation Modeling–Partial Least Square (SEM–PLS) approach, based on secondary data from 21 companies listed on the Indonesia Stock Exchange for the 2018–2024 period. Data processing is carried out using SmartPLS software 4. The results of the study show that only leverage and company size have a significant effect on the company's value in a negative direction. Liquidity has no significant effect, and CSR has no direct influence or role as a mediating variable. These findings show that CSR has not been strategically implemented to increase the company's value. Implicationally, companies need to review their CSR strategies, and further research is suggested to expand the context or add other variables.